Finanzas sostenibles: incidencia del uso del crédito verde en las pymes del cantón Machala en los periodos 2021-2022. - Lino Vera, Nathaly Domenica; Lapo Velez, Maiby Gineth (Machala : Universidad Técnica de Machala, 2024)
Economic and environmental sustainability has become a global business priority. This study investigates the incidence of the use of green credit on Small and Medium Enterprises (PYMES) in Machala Canton during the periods 2021-2022. It examines how PYMES in this region have adopted or been affected by green finance initiatives, focusing on the effects on their financial performance, their ability to implement sustainable practices, and their competitiveness in the marketplace. Quantitative and qualitative methods will be used to analyze financial data, business surveys, and interviews with key actors in the local financial and business sector. The findings of this study will provide relevant information to understand the impact of green credit on PYMES in the region and offer recommendations to promote its adoption and maximize its effectiveness in the future. In a global context of growing environmental awareness and concern for sustainability, small and medium-sized enterprises PYMES play a crucial role in the transition to a greener economy. This study focuses on examining the incidence of the use of green credit in PYMES through a mixed research approach, combining quantitative and qualitative methods, will investigate how PYMES in the region have adopted or have been affected by green credit, and what has been its impact in terms of financial performance, adoption of sustainable practices and market competitiveness.
La sostenibilidad económica y ambiental se ha vuelto una prioridad global en el ámbito empresarial. Este estudio investiga la incidencia del uso del crédito verde en las Pequeñas y Medianas Empresas (Pymes) del Cantón Machala durante los periodos 2021-2022. Se examina cómo las Pymes en esta región han adoptado o se han visto afectadas por iniciativas de financiamiento verde, centrándose en los efectos en su desempeño financiero, su capacidad para implementar prácticas sostenibles y su competitividad en el mercado. Se utilizarán métodos cuantitativos y cualitativos para analizar datos financieros, encuestas a empresarios y entrevistas con actores clave del sector financiero y empresarial local. Los hallazgos de este estudio proporcionarán información relevante para entender el impacto del crédito verde en las Pymes de la región y ofrecerán recomendaciones para promover su adopción y maximizar su efectividad en el futuro. En un contexto global de creciente conciencia ambiental y preocupación por la sostenibilidad, las Pequeñas y Medianas Empresas (Pymes) desempeñan un papel crucial en la transición hacia una economía más verde. Este estudio se centra en examinar la incidencia del uso del crédito verde en las Pymes a través de un enfoque mixto de investigación, que combina métodos cuantitativos y cualitativos, se investigará cómo las Pymes de la región han adoptado o se han visto afectadas por el crédito verde, y cuál ha sido su impacto en términos de desempeño financiero, adopción de prácticas sostenibles y competitividad en el mercado.
Keywords: CREDITO VERDE; FINANZAS; FINANCIAMIENTO; SOSTENIBILIDAD